USE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING THE SUBJECT "TWO MAIN PROBLEMS OF DYNAMICS" - A. G. Qodirov; Y. V. Rojkova; I. U. Abduazimova (American Journals, 2024)
The article presents the methodology of conducting lectures on theoretical mechanics on the topic "Two main problems of dynamics" in the dynamics department. Examples of solving typical problems are given. The use of pedagogical technologies that allow systematic presentation of theoretical material is shown. "Insert" technology allows to evaluate students' knowledge. To strengthen their knowledge, students are invited to solve crossword puzzles and answer questions on the topic of the lecture.
Keywords: Dynamics, point dynamics, mechanical system dynamics, analytical mechanics, inertial force, first and second problems of dynamics, second order differential equation, integral constants, velocity projection, separation into variables.